Parthenogenetic capability of three species in Poa pratensis L. aggregation - K. Szabó, Zsuzsanna; Papp, Mária (Acta Biologica Szegediensis, 2005)
Parthenogenesis, as an asexual reproductive method gives rise to a new prospect in agricultural production: the opportunity to establish genetically stable, seed-propagating clones of crops, which can perpetuate themselves across countless sporophytic generations. Apomictic processes of Poa pratensis has been extensively discussed by several studies. We studied the parthenogenesis capability of species in Poa pratensis L. aggregation collected from seminatural habitats by auxin-test. The article presents that this asexual mode of reproduction occurs in two other species of the Poa pratensis group, in Poa angustifolia and Poa humilis too. The results add more information to the reproductive behavior of these Poa species and could be useful in plant breeding.